1996
DOI: 10.1523/jneurosci.16-11-03590.1996
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Expression of Platelet-Activating Factor Receptor in the Rat Brain Microglia

Abstract: Cellular localization of platelet-activating factor (PAF) receptor in the rat brain was determined by (1) in situ hybridization, (2) Northern blot analysis in primary cell cultures of neurons, microglia, astrocytes, and fibroblasts, and (3) Ca2+ imaging in hippocampal culture. In situ hybridization revealed that the PAF receptor mRNA is expressed intensely in microglia and moderately in neurons. Northern blot analysis revealed that PAF receptor mRNA is the most abundant in microglia. In primary hippocampal cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 79 publications
3
67
0
1
Order By: Relevance
“…We also reported that arachidonic acid is released from these cells (Mori et al 1996). In the present study, we found that PAF causes a prominent chemotactic response in the activated microglia (Fig.…”
Section: Chemotactic Response Of Microglia To Pafsupporting
confidence: 77%
See 1 more Smart Citation
“…We also reported that arachidonic acid is released from these cells (Mori et al 1996). In the present study, we found that PAF causes a prominent chemotactic response in the activated microglia (Fig.…”
Section: Chemotactic Response Of Microglia To Pafsupporting
confidence: 77%
“…Taken together, these observations strongly suggest that PAF plays crucial roles in the central nervous system. We previously reported that PAFR is present in the brain (Bito et al 1992;Mori et al 1996) and stimulates intracellular increases in calcium and arachidonic acid release in microglia (Mori et al 1996). Also consistent with a role for PAF in the brain, investigators have demonstrated the stimulation of PAF synthesis in the presence of acetylcholine (Sogos et al 1990) or dopamine (Bussolino et al 1986), as well as during convulsant electrical stimuli (Kumar et al 1988), ischaemia (Baker & Chang 1993,1994Kunievsky & Yavin 1994;Francescangeli et al 1996) or viral infection (Gelbard et al 1994;.…”
Section: Introductionmentioning
confidence: 76%
“…ATP has been deemed a putative signaling agent released by neurons after cellular damage and may serve as an activating factor for microglia (Norenberg et al, 1994). PAF has also been suggested as an activating factor for microglia (Mori et al, 1996) and is synthesized in the brain by glia, neurons, endothelial cells, and blood-borne leukocytes after ischemic injury (Yue et al, 1994). PAF has also been indicated to have an important role in mediating CNS injury.…”
Section: Introductionmentioning
confidence: 99%
“…PAF has also been indicated to have an important role in mediating CNS injury. Mori et al (1996) have reported that PAF is able to induce arachidonic acid metabolism in microglia, potentially resulting in the production of neurotoxic factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has documented a diversity of agents which cause transient increases in levels of cytoplasmic Ca 2+ in rodent microglia; such responses may be involved in coupling activating stimuli to particular cellular functions. Among the spectrum of stimuli found to elicit transient Ca 2+ responses in cultured rodent cells are complement [1], ATP [2][3][4], carbachol [5], platelet-activating factor (PAF [6]) and endothelin [7]. All of these stimuli (complement has not yet been tested) have also been found to cause transient Ca 2+ responses in human microglia [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%